Circulating cell adhesion molecules in systemic sclerosis: a systematic review and meta-analysis - Mangoni, Arduino A.; Zinellu, Angelo (Frontiers in Immunology, 2024)
Patients with systemic sclerosis (SSc) have an increased risk of endothelial dysfunction, atherosclerosis, and cardiovascular events compared to the general population. Therefore, the availability of robust circulating biomarkers of endothelial dysfunction and atherogenesis may facilitate early recognition and management of cardiovascular risk in SSc. We sought to address this issue by conducting a systematic review and meta-analysis of studies investigating various types of circulating cell adhesion molecules involved in endothelial dysfunction and atherogenesis (i.e., immunoglobulin-like vascular cell, VCAM-1, intercellular, ICAM-1, platelet endothelial cell, PECAM-1, neural cell, NCAM, Down syndrome cell, DSCAM, and endothelial cell-selective, ESAM, adhesion molecules, E-, L-, and P-selectin, integrins, and cadherins) in SSc patients and healthy controls. We searched PubMed, Scopus, and Web of Science from inception to 1 May 2024. Risk of bias and certainty of evidence were assessed using validated tools. In 43 eligible studies, compared to controls, patients with SSc had significantly higher plasma or serum concentrations of ICAM-1 (standard mean difference, SMD=1.16, 95% CI 0.88 to 1.44, p<0.001; moderate certainty), VCAM-1 (SMD=1.09, 95% CI 0.72 to 1.46, p<0.001; moderate certainty), PECAM-1 (SMD=1.65, 95% CI 0.33 to 2.98, p=0.014; very low certainty), E-selectin (SMD=1.17, 95% CI 0.72 to 1.62, p<0.001; moderate certainty), and P-selectin (SMD=1.10, 95% CI 0.31 to 1.90, p=0.007; low certainty). There were no significant between-group differences in L-selectin concentrations (SMD=-0.35, 95% CI -1.03 to 0.32, p=0.31; very low certainty), whereas minimal/no evidence was available for cadherins, NCAM, DSCAM, ESAM, or integrins. Overall, no significant associations were observed between the effect size and various patient and study characteristics in meta-regression and subgroup analyses. The results of this systematic review and meta-analysis suggest that specific circulating cell adhesion molecules, i.e., ICAM-1, VCAM-1, PECAM-1, E-selectin, and P-selectin, can be helpful as biomarkers of endothelial dysfunction and atherogenesis in the assessment of cardiovascular risk in SSc patients. (PROSPERO registration number, CRD42024549710).